Pendidikan Humanis dalam Perspektif Hadis (Kajian Kitab Shaḥīh Al-Bukhārī) - Musdalifah; Tasbih; Subehan Khalik (Jurnal Pendidikan Kreatif, 2025)
Humanist education emphasizes human values, respect for individual dignity, and the holistic development of self-potential. In the perspective of Islam, this concept correlates with teachings found in the hadith, particularly those compiled in the Ṣaḥīḥ al-Bukhārī. This article explores the concept of humanist education through an analysis of hadiths in Ṣaḥīḥ al-Bukhārī, covering aspects such as respect for individual rights, freedom of thought, empathy, and character development. Using a descriptive analysis method, this study finds that humanist education has a strong foundation in Islamic values, with hadiths encouraging the cultivation of positive attitudes and harmonious relationships within society. This shows that humanist education in Islam is an integral part of educational goals that honor humanity.